Current State of Psychopharmacology, Psychotherapies and Other Interventions in Mental Health Problems and Disorders - BERTOLÍN-GUILLÉN, José Manuel (European Journal of Applied Sciences, 2021)
Proposal: The article broadly aims to emphasise the current relevance of physical and psychological treatments for most mental and behavioural disorders. Design: Critical analysis and reasoned opinion of a selected compilation of the best, widely read, high-quality scientific literature. Methodologically, it is a brief meta-synthetic review. Results and interpretation: In general, for almost all mental disorders, combined treatment with psychotropic drugs and psychotherapy seems to be more effective than psychotherapy or pharmacotherapy alone. Particularly in Spain (European Union), the risk for psychotherapies of therapeutic intrusion by non-specialists who are not medical psychiatrists or clinical psychologists is high. A similar situation occurs with the routine prescription of psychotropic drugs by other physicians. The frequent stigma associated with any mental pathology is then addressed, as well as the obligation to obtain informed consent for any therapeutic intervention. Lastly, mention is made of the usefulness of the personal state of full awareness, more commonly called mindfulness, training for which is included in numerous help programmes based on its continued practice, whether or not mental disorders are diagnosed. Conclusions: More randomised clinical trials with low risk of bias and accidental errors are needed to properly assess the effects of psychotherapeutic interventions. From a scientific perspective, based on multiple evidence, the efficacy of properly prescribed psychopharmacotherapy is not in question.